Agronomic Performance of European Pear Cultivars in Different Training Systems in the Highland Region of Southern Brazil - Alex Felix Dias; Sabrina Baldissera; Alberto Ramos Luz; Augusto Schütz Ferreira; Bruno Dalazen Machado; Bruno Pirolli; Renaldo Borges de Andrade Júnior; Joel de Castro Ribeiro; Daiana Petry Rufato; Aike Anneliese Kretzschmar; Amauri Bogo; Leo Rufato (Agriculture)
This study aimed to evaluate the vegetative, productive, and fruit quality parameters of the European pear cultivars ‘Rocha’ and ‘Santa Maria’ under the training systems of Tall Spindle, with branches bent at an angle of 45° (Tall Spindle—45°) and 90° (Tall Spindle—90°) to the leader, and Bi-axis. The evaluation was conducted over the 2016/2017 to 2022/2023 growing seasons in the highland region of southern Brazil. Both Tall Spindle systems significantly improved the yield and productive efficiency compared to the Bi-axis system, with ‘Santa Maria’ showing superior performance under Tall Spindle—90°. While ‘Rocha’ exhibited no significant differences between Tall Spindle systems, it benefited from better vigor control and reduced biennial bearing when trained under the Bi-axis system. Fruit quality parameters were consistent across training systems, indicating Tall Spindle—90° as an optimal choice for productivity and stability in ‘Santa Maria’. These results emphasize the adaptability and efficiency of training systems for pear orchard management.